Modern contraceptive method utilization among mothers of children aged 7 to 24 months at the Yalgado Ouédraogo University Hospital, Burkina Faso, West Africa - Kiemtoré, Sibraogo; Sawadogo, Yobi A.; Ouédraogo, Issa; Komboigo, Evelyne B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study aimed to examine the use of modern contraceptive methods among mothers of children aged 7 to 24 Months at Yalgado Ouédraogo University Hospital (CHU-YO) in Ouagadougou, Burkina Faso. Methods: An analytical cross-sectional survey was conducted among 412 women who had delivered at CHU-YO and whose infants were between 7 and 24 months of age. A structured questionnaire was used to collect data on sociodemographic characteristics, obstetric history, and modern contraceptive use. Data analysis using R software identified associations between modern contraceptive use and various factors. Results: The study found a 69.2% prevalence of modern contraceptive use among participants. The progestin implant and intrauterine device (IUDs) were the most commonly used methods. Factors associated with modern method use included age over 30 years, higher level of education, having at least two living children, having received family planning counseling, and having given birth by cesarean section. Factors associated with the use of long-acting methods in the multivariate analysis were being married, having received family planning counseling during pregnancy or in the postpartum period, having had a cesarean delivery, and being overweight (BMI ³ 24.5 kg/m2). Factors associated with the use of hormonal methods in multivariate analysis were having received family planning counseling during pregnancy or in the postpartum period and having had a vaginal delivery. Conclusions: The use of modern contraceptive methods was higher among mothers of children aged 7 to 24 months than in the general population. However, factors such as age, level of education and having received family planning advice influenced women's contraceptive use. Health professionals need to explore ways to further improve the use of modern contraceptives.